Thermoelectric cement-based composite material and preparation method and application thereof
By adding graphene and ionic liquids to the thermal power cement base composite material, the "ion-electron 'hybrid thermal power effect is used to solve the problem of the existing thermoelectric cement base composite material SEEBECK coefficient and low conductivity, realizing the performance improvement of the material And cost control.
Patent Information
- Application Number
- CN202310187383.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-02-21
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2043-02-21
AI Technical Summary
The Seebeck coefficient and conductivity of existing thermoelectric cement matrix composite materials are low and cannot be effectively applied to actual engineering. At the same time, high-dose functional fillers will increase production costs and affect the mechanical and durability of the material.
Adopt graphene and ionic liquids in silicate cement matrix. Graphene as an electronic thermoelectric component provides an empty cavity carrier, ionic liquid is used as a P-type ion thermoelectric component to provide ionic thermoelectric effects. The effect is significantly improved SEEBECK coefficient and conductivity.
Achieve the improvement of the Seebeck coefficient and conductivity on the basis of ensuring mechanical performance, durability and economics, and the low content of graphene can significantly improve the SEEBECK coefficient. Electronic conductivity.
Smart Images

Figure CN116283137B_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of thermoelectric materials, and in particular to a thermoelectric cement-based composite material and a preparation method and application thereof. Background Art
[0002] Because traditional fossil fuels are consumed too quickly and are prone to environmental pollution. The demand for alternative energy sources is growing. Among them, thermoelectric materials that can convert thermal energy into electrical energy have been a hot topic of research in recent years. Thermoelectric effect (Seebeck effect) refers to the thermal diffusion of carriers inside a material when it is subjected to a temperature gradient, thereby generating a thermovoltage. Traditional thermoelectric materials are mainly solid materials such as metals and semiconductors. Such thermoelectric materials use the thermal diffusion of electrons or holes to generate thermovoltage, also known as the thermoelectric effect (Seebeck effect). In recent years, scholars from various countries have obtained electronic thermoelectric cement-based composites with significant electronic thermoelectric effects by adding various functional fillers to the cement matrix. In related studies, adding high amounts (mass percentage of about 20% or more) of functional fillers, such as carbon materials and metal oxides, to cement-based materials has become the main strategy for improving the thermoelectric effect of cement-based composites. However, the Seebeck coefficient of cement-based composites doped with carbon materials is basically below 100μV / K, which cannot be applied to actual engineering projects, and the doping amount is relatively high; although the Seebeck coefficient of cement-based composites doped with metal oxides can reach above 1000μV / K, since metal oxides cannot effectively improve the electrical conductivity of cement-based materials, their thermoelectric efficiency is still low.
[0003] In order to further improve the thermoelectric effect of cement-based composite materials, the types of functional fillers added to cement-based materials are increasing, and the dosage is increasing, which will significantly increase the production cost of cement-based composite materials. In addition, high dosage of functional fillers will affect the hydration reaction of cement particles and deteriorate the mechanical properties and durability of cement-based materials. Summary of the invention
[0004] Based on this, it is necessary to provide a thermoelectric cement-based composite material capable of improving the Seebeck coefficient and electrical conductivity, and a preparation method and application thereof.
[0005] In a first aspect, the present application provides a thermoelectric cement-based composite material, which includes a silicate cement matrix, graphene and an ionic liquid, wherein the graphene is dispersed in the silicate cement matrix, the mass ratio of the silicate cement matrix to the graphene is 100:(0.05-0.15), and the ionic liquid is filled in the pores of the silicate cement matrix.
[0006] In some embodiments, a water reducing agent is further included in the silicate cement matrix, and the mass ratio of the silicate cement matrix to the water reducing agent is 100:(0.1-0.3).
[0007] In some embodiments, the water reducer is a polycarboxylic acid-based water reducer.
[0008] In some embodiments, the ionic liquid comprises [BMIm][TFSI], [EMIm][Ac], [BMIm][PF 6 ], [EMIm][TFSI], [OMIm][Ac] and [OMIm][TFSI] or more.
[0009] In some embodiments, the porosity of the silicate cement matrix is 18% to 25%.
[0010] In some embodiments, the strength grade of the Portland cement matrix is 42.5 or 52.5.
[0011] In some embodiments, the thickness of the graphene is 4 nm to 20 nm, the width of a single-layer graphene is 5 μm to 10 μm, and the number of layers is less than 30.
[0012] In a second aspect, the present application further provides a method for preparing the cement-based composite material as described in the first aspect, comprising the following steps:
[0013] Mixing silicate cement and the graphene in water to form a slurry, wherein the mass ratio of silicate cement to graphene is 100:(0.05-0.15);
[0014] Placing the slurry in a mold for shaping and curing to form a silicate cement matrix in which graphene is dispersed; and
[0015] The ionic liquid is filled into the pores of the silicate cement matrix by vacuum saturation.
[0016] In some embodiments, the vacuum degree of the vacuum saturation is ≤0.098Pa.
[0017] In some embodiments, the water-cement ratio of the water to the Portland cement is 0.4-0.6.
[0018] In some embodiments, before the slurry is placed in a mold for forming, a step of mixing a water reducing agent into the slurry is also included; the mass ratio of the silicate cement to the water reducing agent is 100:(0.1-0.3).
[0019] In a third aspect, the present application further provides an application of the cement-based composite material described in the first aspect as a thermoelectric material.
[0020] The thermoelectric cement-based composite material provided by the present application uses graphene, a two-dimensional nanomaterial with significant thermoelectric effect, as a functional filler in the composite material, which can provide a large number of hole carriers for the composite material, so that it has a p-type thermoelectric effect, obtains a higher Seebeck coefficient, and has the advantages of low cost and mass production. Moreover, the thermoelectric cement-based composite material provided by the present application can significantly improve the Seebeck coefficient by adding a low content of graphene, and graphene can provide a large number of hole carriers as an electronic thermoelectric component. At the same time, ionic liquids, i.e., p-type ionic thermoelectric components, are filled in the pores of the cement matrix to provide ionic thermoelectric effects. Under the action of temperature difference, the ionic carriers and electronic carriers inside the thermoelectric cement-based composite material work together, that is, the Seebeck coefficient of the composite material is significantly improved through the "ion-electron" mixed thermoelectric effect, and its electrical conductivity is improved.
[0021] In addition, since the ionic liquid itself is a polymer material, it does not react with the cement matrix, thereby improving the stability of the ionic thermoelectric effect. Moreover, by introducing the ionic liquid as an ion conductive material, the interface resistance between the graphene sheets in the cement matrix is reduced, further improving the electronic conductivity of the thermoelectric cement-based composite material. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] In order to more clearly illustrate the specific implementation methods of the present application or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.
[0023] Figure 1 Schematic diagram of the preparation process of a thermoelectric cement-based composite material in one embodiment. DETAILED DESCRIPTION
[0024] In order to facilitate the understanding of the present application, the present application will be described more fully below with reference to the relevant drawings. The preferred embodiments of the present application are given in the drawings. However, the present application can be implemented in many different forms and is not limited to the embodiments described herein. On the contrary, the purpose of providing these embodiments is to make the understanding of the disclosure of the present application more thorough and comprehensive.
[0025] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those generally understood by those skilled in the art to which the present application belongs. The terms used herein in the specification of the present application are only for the purpose of describing specific embodiments and are not intended to limit the present application. The term "and / or" used herein includes any and all combinations of one or more of the related listed items.
[0026] Except as shown in the operating examples or otherwise indicated, all numbers used in the specification and claims to indicate the amount of ingredients, physicochemical properties, etc. are understood to be adjusted by the term "about" in all cases. For example, therefore, unless otherwise indicated, the numerical parameters listed in the above specification and the attached claims are approximate values, and those skilled in the art can use the teachings disclosed herein to seek to obtain the desired properties and appropriately change these approximate values. The use of numerical ranges expressed as endpoints includes all numbers within the range and any range within the range, for example, 1 to 5 includes 1, 1.1, 1.3, 1.5, 2, 2.75, 3, 3.80, 4 and 5, etc.
[0027] Traditional methods of improving the thermoelectric effect of thermoelectric cement-based composite materials usually cannot significantly and effectively improve their thermoelectric coefficient and electrical conductivity, and will lead to a decrease in their mechanical properties and durability. At the same time, a high amount of functional fillers will increase the preparation cost. To this end, the present application provides a thermoelectric cement-based composite material and its preparation method and application, which can achieve the improvement of the Seebeck coefficient and electrical conductivity of cement-based composite materials while ensuring mechanical properties, durability and economy.
[0028] In a first aspect, the present application provides a thermoelectric cement-based composite material, which includes a silicate cement matrix, graphene and an ionic liquid, wherein the graphene is dispersed in the silicate cement matrix, the mass ratio of the silicate cement matrix to the graphene is 100:(0.05-0.15), and the ionic liquid is filled in the pores of the silicate cement matrix.
[0029] The above-mentioned thermoelectric cement-based composite material uses graphene, a two-dimensional nanomaterial with significant thermoelectric effect, as a functional filler in the composite material, which can provide a large number of hole carriers for the composite material, so that it has a p-type thermoelectric effect, obtains a higher Seebeck coefficient, and has the advantages of low cost and mass production. Moreover, the thermoelectric cement-based composite material provided by the present application can achieve a significant improvement in the Seebeck coefficient by adding a low content of graphene, and graphene can provide an electronic thermoelectric effect. At the same time, ionic liquids, i.e., p-type ionic thermoelectric components, are filled in the pores of the composite material to provide an ionic thermoelectric effect. Under the action of temperature difference, the ionic carriers and electronic carriers inside the thermoelectric cement-based composite material work together, that is, the Seebeck coefficient of the composite material is significantly improved through the "ion-electron" mixed thermoelectric characteristics, and its electrical conductivity is improved.
[0030] In addition, since the ionic liquid itself is a polymer material, it does not react with the cement matrix, thereby improving the stability of the ionic thermoelectric effect. Moreover, by introducing the ionic liquid as an ion conductive material, the interface resistance between the graphene sheets in the cement matrix is reduced, further improving the electronic conductivity of the thermoelectric cement-based composite material.
[0031] In some embodiments, the mass ratio of silicate cement to graphene is any value between 100:(0.05-0.15), and can also be 100:0.06, 100:0.07, 100:0.08, 100:0.09, 100:0.10, 100:0.11, 100:0.12, 100:0.13, 100:0.14. By regulating the mass ratio of graphene to silicate cement within this range, the thermoelectric effect of the thermoelectric cement-based composite material can be maximized on the basis of ensuring uniform and stable dispersion of graphene.
[0032] In order to improve the fluidity and processability of silicate cement, a water reducer may be mixed into the silicate cement matrix, that is, the water reducer is uniformly added into the silicate cement matrix. In the present application, the content and type of the water reducer are not specifically limited, and the water reducer and content commonly used in the cement processing field may be selected. In some embodiments, the mass ratio of silicate cement to the water reducer is any value between 100:(0.1 to 0.3), and may also be 100:0.15, 100:0.2, and 100:0.25. The water reducer may specifically be a polycarboxylic acid-based water reducer.
[0033] It is understood that the strength grade of the silicate cement matrix specifically refers to the compressive strength achieved after curing for 28 days under standard conditions. The strength grade of the silicate cement matrix is generally divided into three grades and six types, as follows: 42.5, 42.5R, 52.5, 52.5R, 62.5, 62.5R. In some embodiments, the strength grade of the silicate cement matrix is 42.5 or 52.5.
[0034] In some embodiments, the thickness of graphene is 4nm to 20nm, and can also be 5nm, 8nm, 10nm, 12nm, 15nm, and 18nm; the width of a single layer of graphene is 5μm to 10μm, and can also be 6μm, 7μm, 8μm, and 9μm; the number of layers is less than 30 layers.
[0035] In the present application, the ionic liquid is mainly an imidazole ionic liquid. In some embodiments, the ionic liquid includes 1-butyl-3-methylimidazolium bistrifluoromethanesulfonyl imide salt ([BMIm][TFSI]) ionic liquid, 1-ethyl-3-methylimidazolium acetate ([EMIm][Ac]) ionic liquid, 1-butyl-3-methylimidazolium hexafluorophosphate ([BMIm][PF 6 ]) ionic liquid, 1-ethyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide salt ([EMIm][TFSI]) ionic liquid, 1-octyl-3-methylimidazolium acetate ([OMIm][Ac]) ionic liquid and 1-octyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide salt [OMIm][TFSI] ionic liquid or more.
[0036] In the present application, the porosity of the silicate cement matrix is not limited. In some embodiments, the porosity of the silicate cement matrix is 18% to 25%. It is understood that by regulating the porosity of the silicate cement matrix, the proportion of the ionic liquid in the silicate cement matrix can be regulated.
[0037] like Figure 1 As shown, in a second aspect, the present application also provides a method for preparing the thermoelectric cement-based composite material as described in the first aspect, comprising the following steps:
[0038] Step S10: mixing silicate cement and graphene in water to form a slurry, wherein the mass ratio of silicate cement to graphene is 100:(0.05-0.15);
[0039] Step S20: placing the slurry in a mold for shaping and curing to form a silicate cement matrix in which graphene is dispersed;
[0040] Step S30: Filling the pores of the silicate cement matrix with the ionic liquid by vacuum saturation.
[0041] It is understood that the specific method of mixing silicate cement and graphene in water to form a slurry can be as follows:
[0042] Method 1: Mix silicate cement and graphene together and place in water to form a slurry;
[0043] Method 2: Firstly, graphene is dispersed in water to form a graphene dispersion; then, silicate cement is dispersed in the graphene dispersion to form a slurry;
[0044] Method three: first disperse silicate cement and graphene in water respectively to form cement slurry and graphene dispersion; then mix the cement slurry and graphene dispersion to form slurry.
[0045] It is understood that the curing time is usually 28 days. Curing can prevent the water in the cement from evaporating too quickly and causing dehydration, so that the cement particles that have formed gel can be fully hydrated and transformed into stable crystals, forming sufficient bonding force, so as not to cause flaking or powdery shedding on the cement surface. In addition, the cement does not have sufficient strength in the early stage of molding, and the premature evaporation of water will also cause large shrinkage deformation and shrinkage cracks, which can be avoided through curing.
[0046] In some embodiments, the vacuum degree of vacuum saturation is ≤ 0.098 Pa.
[0047] In some embodiments, the water-cement ratio of water to Portland cement is 0.4 to 0.6. Preferably, the water-cement ratio of water to Portland cement is 0.6. It can be understood that by adjusting the water-cement ratio of water to Portland cement, the porosity of the Portland cement matrix can be adjusted.
[0048] In a third aspect, the present application further provides an application of the thermoelectric cement-based composite material described in the first aspect as a thermoelectric material.
[0049] The present application is further described in detail below in conjunction with specific embodiments.
[0050] In the following embodiments and comparative examples, the graphene is a highly conductive graphene from Shanxi Coal Chemistry Research, Chinese Academy of Sciences, with a graphene thickness of 4 nm to 20 nm, a single-layer graphene width of 5 μm to 10 μm, and a number of layers of less than 30; and the strength grade of silicate cement is 42.5.
[0051] Example 1
[0052] 1) Weigh silicate cement, water, graphene and polycarboxylic acid water reducer in a mass ratio of 100:60:0.15:0.1 and set aside;
[0053] 2) Add graphene to water and stir mechanically for 5 minutes to form a suspension, and then use an ultrasonic disperser to ultrasonically disperse at a power of 400W for 30 minutes to obtain a uniformly dispersed graphene suspension. Then, add silicate cement and polycarboxylic acid water reducer to the graphene suspension in turn, and use a planetary mixer to slowly stir for 5 minutes at a speed of 60rpm / min, and then quickly stir for 10 minutes at a speed of 130rpm / min. After it is evenly stirred, pour it into a stainless steel mold with a size of 20mm×20mm×80mm to form it, and then after closed curing for 28 days, a graphene-enhanced cement-based composite material can be made. Subsequently, after winding a conductive copper wire around both ends of the graphene-enhanced cement-based composite material and coating it with conductive silver paste, a hot drying gun is used to dry it to make an electrode. The electrode is then placed in an oven at 80°C and dried for 24 hours;
[0054] 3) The graphene-enhanced cement-based composite material dried in step 2) is immersed in 1-ethyl-3-methylimidazolium acetate ionic liquid [Emim][Ac] and vacuum saturated for 24 hours to fill the pores of the graphene-enhanced cement-based composite material with the ionic liquid, encapsulated, and prepared a thermoelectric cement-based composite material.
[0055] The relevant properties of the above-mentioned thermoelectric cement-based composite materials are tested as follows:
[0056] The Seebeck coefficient of the tested thermoelectric cement-based composite material is 2317.56 μV / K, and the conductivity is calculated to be 0.021 S / m according to the following formula;
[0057] Conductivity calculation formula:
[0058] σ=l / (sR)
[0059] Wherein, σ is the conductivity, l is the length of the specimen, s is the area of the end of the specimen, and R is the resistance; in this embodiment, l is 80 mm, s is 400 mm 2 .
[0060] Example 2
[0061] 1) Weigh silicate cement, water, graphene and polycarboxylic acid water reducer in a mass ratio of 100:60:0.05:0.1 and set aside;
[0062] 2) Add graphene to water and stir mechanically for 5 minutes to form a suspension, and then use an ultrasonic disperser to ultrasonically disperse at a power of 400W for 30 minutes to obtain a uniformly dispersed graphene suspension. Then, add silicate cement and polycarboxylic acid water reducer to the graphene suspension in turn, and use a planetary mixer to slowly stir for 5 minutes at a speed of 60rpm / min, and then quickly stir for 10 minutes at a speed of 130rpm / min. After it is evenly stirred, pour it into a stainless steel mold with a size of 20mm×20mm×80mm to form it, and then after closed curing for 28 days, a graphene-enhanced cement-based composite material can be made. Subsequently, after winding a conductive copper wire around both ends of the graphene-enhanced cement-based composite material and coating it with conductive silver paste, a hot drying gun is used to dry it to make an electrode. The electrode is then placed in an oven at 80°C and dried for 24 hours;
[0063] 3) The graphene-enhanced cement-based composite material dried in step 2) is immersed in 1-ethyl-3-methylimidazolium acetate ionic liquid [Emim][Ac] and vacuum saturated for 24 hours to fill the pores of the graphene-enhanced cement-based composite material with the ionic liquid, encapsulated, and prepared a thermoelectric cement-based composite material.
[0064] The relevant properties of the above-mentioned thermoelectric cement-based composite materials are tested as follows:
[0065] The Seebeck coefficient of the tested thermoelectric cement-based composite material is 897.21μV / K, and the conductivity is calculated to be 0.024S / m;
[0066] In this embodiment, l is 80 mm and s is 400 mm. 2 .
[0067] Example 3
[0068] 1) Weigh silicate cement, water, graphene and polycarboxylic acid water reducer in a mass ratio of 100:60:0.15:0.1 and set aside;
[0069] 2) Add graphene to water and stir mechanically for 5 minutes to form a suspension, and then use an ultrasonic disperser to ultrasonically disperse at a power of 400W for 30 minutes to obtain a uniformly dispersed graphene suspension. Then, add silicate cement and polycarboxylic acid water reducer to the graphene suspension in turn, and use a planetary mixer to slowly stir for 5 minutes at a speed of 60rpm / min, and then quickly stir for 10 minutes at a speed of 130rpm / min. After it is evenly stirred, pour it into a stainless steel mold with a size of 20mm×20mm×80mm to form it, and then after closed curing for 28 days, a graphene-enhanced cement-based composite material can be made. Subsequently, after winding a conductive copper wire around both ends of the graphene-enhanced cement-based composite material and coating it with conductive silver paste, a hot drying gun is used to dry it to make an electrode. The electrode is then placed in an oven at 80°C and dried for 24 hours;
[0070] 3) The graphene-enhanced cement-based composite material dried in step 2) is immersed in 1-octyl-3-methylimidazolium acetate ionic liquid ([OMIm][Ac]) and vacuum saturated for 24 hours to fill the pores of the graphene-enhanced cement-based composite material with the ionic liquid, encapsulated, and prepared a thermoelectric cement-based composite material.
[0071] The relevant properties of the above-mentioned thermoelectric cement-based composite materials are tested as follows:
[0072] The Seebeck coefficient of the thermoelectric cement-based composite material was tested to be 2171.69 μV / K, and the conductivity was calculated to be 0.022 S / m;
[0073] In this embodiment, l is 80 mm and s is 400 mm. 2 .
[0074] Comparative Example 1
[0075] The preparation method of Comparative Example 1 is substantially the same as that of Example 1, except that no graphene is added. The specific steps are as follows:
[0076] 1) Weigh silicate cement, water and polycarboxylic acid water reducer in a mass ratio of 100:60:0.1 and set aside;
[0077] 2) Mix the silicate cement and the polycarboxylic acid water reducer, and use a planetary mixer to slowly stir for 5 minutes at 60rpm / min, and then quickly stir for 10 minutes at 130rpm / min. After stirring evenly, pour it into a stainless steel mold with a size of 20mm×20mm×80mm to form it. After closed curing for 28 days, the cement-based composite material can be made. Subsequently, after winding conductive copper wires at both ends of the cement-based composite material and coating them with conductive silver paste, use a hot drying gun to dry it to make electrodes. Then place the electrodes in an oven at 80°C and dry them for 24 hours;
[0078] 3) The cement-based composite material dried in step 2) is immersed in 1-ethyl-3-methylimidazolium acetate ionic liquid [Emim][Ac] and vacuum saturated for 24 hours to fill the pores of the cement-based composite material with the ionic liquid, and encapsulated to prepare a thermoelectric cement-based composite material.
[0079] The relevant properties of the above-mentioned thermoelectric cement-based composite materials are tested as follows:
[0080] The Seebeck coefficient of the thermoelectric cement-based composite material was tested to be 507.95 μV / K, and the conductivity was calculated to be 0.026 S / m according to the following formula;
[0081] In this comparative example, l is 80 mm and s is 400 mm. 2 .
[0082] Comparative Example 2
[0083] The preparation method of Comparative Example 2 is substantially the same as that of Example 1, except that step 3) is not performed, that is, the graphene-enhanced cement-based composite material is not immersed in the ionic liquid. The specific steps are as follows:
[0084] 1) Weigh silicate cement, water, graphene and polycarboxylic acid water reducer in a mass ratio of 100:60:0.15:0.1 and set aside;
[0085] 2) Add graphene to water and stir mechanically for 5 minutes to form a suspension, and then use an ultrasonic disperser to ultrasonically disperse for 30 minutes at a power of 400W to obtain a uniformly dispersed graphene suspension. Then, silicate cement and polycarboxylic acid water reducer are added to the graphene suspension in sequence, and a planetary mixer is used to slowly stir for 5 minutes at a speed of 60rpm / min, and then quickly stir for 10 minutes at a speed of 130rpm / min. After stirring evenly, pour it into a stainless steel mold with a size of 20mm×20mm×80mm to form, and then after closed curing for 28 days, a graphene-enhanced cement-based composite material can be prepared. Subsequently, after winding a conductive copper wire at both ends of the graphene-enhanced cement-based composite material and coating it with conductive silver paste, a hot drying gun is used to dry it to make an electrode. The electrode is then placed in an oven at 80°C for 24 hours to prepare a thermoelectric cement-based composite material.
[0086] The Seebeck coefficient of the tested thermoelectric cement-based composite material is 1971.66 μV / K, and the conductivity is calculated to be 0.020 S / m according to the following formula;
[0087] In this comparative example, l is 20 mm and s is 400 mm. 2 .
[0088] Comparative Example 3
[0089] The preparation method of comparative example 3 is substantially the same as that of example 1, except that the water-cement ratio of the graphene-enhanced cement-based composite material is 0.4. The specific steps are as follows:
[0090] 1) Weigh silicate cement, water, graphene and polycarboxylic acid water reducer in a mass ratio of 100:40:0.15:0.1 and set aside;
[0091] 2) Add graphene to water and stir mechanically for 5 minutes to form a suspension, and then use an ultrasonic disperser to ultrasonically disperse at a power of 400W for 30 minutes to obtain a uniformly dispersed graphene suspension. Then, add silicate cement and polycarboxylic acid water reducer to the graphene suspension in turn, and use a planetary mixer to slowly stir for 5 minutes at a speed of 60rpm / min, and then quickly stir for 10 minutes at a speed of 130rpm / min. After it is evenly stirred, pour it into a stainless steel mold with a size of 20mm×20mm×80mm to form it, and then after closed curing for 28 days, a graphene-enhanced cement-based composite material can be made. Subsequently, after winding a conductive copper wire around both ends of the graphene-enhanced cement-based composite material and coating it with conductive silver paste, a hot drying gun is used to dry it to make an electrode. The electrode is then placed in an oven at 80°C and dried for 24 hours;
[0092] 3) The graphene-enhanced cement-based composite material dried in step 2) is immersed in 1-ethyl-3-methylimidazolium acetate ionic liquid [Emim][Ac] and vacuum saturated for 24 hours to fill the pores of the graphene-enhanced cement-based composite material with the ionic liquid, encapsulated, and prepared a thermoelectric cement-based composite material.
[0093] The Seebeck coefficient of the tested thermoelectric cement-based composite material is 1859.23 μV / K, and the conductivity is calculated to be 0.018 S / m according to the following formula;
[0094] In this comparative example, l is 20 mm and s is 400 mm. 2 .
[0095] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0096] The above-mentioned embodiments only express several implementation methods of the present application, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for a person of ordinary skill in the art, several variations and improvements can be made without departing from the concept of the present application, and these all belong to the protection scope of the present application. Therefore, the protection scope of the patent of the present application shall be subject to the attached claims, and the specification and drawings may be used to interpret the scope of the claims.
Claims
1. A thermoelectric cement-based composite material, characterized in that: It comprises a silicate cement matrix, graphene and an ionic liquid, wherein the graphene is dispersed in the silicate cement matrix, the mass ratio of the silicate cement matrix to the graphene is 100:(0.05-0.15), and the ionic liquid is filled in the pores of the silicate cement matrix; the ionic liquid comprises one or more of [BMIm][TFSI], [EMIm][Ac], [BMIm][PF6], [EMIm][TFSI], [OMIm][Ac] and [OMIm][TFSI]; The porosity of the silicate cement matrix is 18% to 25%; The preparation method of the thermoelectric cement-based composite material comprises the following steps: Mixing silicate cement and the graphene in water to form a slurry, wherein the mass ratio of silicate cement to graphene is 100:(0.05-0.15); Placing the slurry in a mold for shaping and curing to form a silicate cement matrix in which graphene is dispersed; and The ionic liquid is filled into the pores of the silicate cement matrix by vacuum saturation.
2. The thermoelectric cement-based composite material according to claim 1, characterized in that: It also includes a water reducing agent mixed in the silicate cement matrix, and the mass ratio of the silicate cement matrix to the water reducing agent is 100: (0.1-0.3).
3. The thermoelectric cement-based composite material according to claim 2, characterized in that: The water reducing agent is a polycarboxylic acid water reducing agent.
4. The thermoelectric cement-based composite material according to any one of claims 1 to 3, characterized in that: The strength grade of the silicate cement matrix is 42.5 or 52.
5.
5. The thermoelectric cement-based composite material according to any one of claims 1 to 3, characterized in that: The thickness of the graphene is 4nm-20nm, the width of a single-layer graphene is 5μm-10μm, and the number of layers is less than 30.
6. A method for preparing a thermoelectric cement-based composite material according to any one of claims 1 to 5, characterized in that: The following steps are involved: Mixing silicate cement and the graphene in water to form a slurry, wherein the mass ratio of silicate cement to graphene is 100:(0.05-0.15); Placing the slurry in a mold for shaping and curing to form a silicate cement matrix in which graphene is dispersed; and The ionic liquid is filled into the pores of the silicate cement matrix by vacuum saturation.
7. The preparation method according to claim 6, characterized in that: The vacuum degree of the vacuum saturation is ≤0.098Pa.
8. The preparation method according to claim 6, characterized in that: The water-cement ratio of the water to the silicate cement is 0.4-0.
6.
9. The preparation method according to any one of claims 6 to 8, characterized in that: Before the slurry is placed in a mold for forming, the method further includes mixing a water reducing agent into the slurry; the mass ratio of the silicate cement to the water reducing agent is 100:(0.1-0.3).
10. Use of the thermoelectric cement-based composite material according to any one of claims 1 to 5 as a thermoelectric material.
Citation Information
Patent Citations
Ionic liquid filling type porous silicon optical VOC sensor array and preparation method thereof
CN103353447A
Method for improving thermoelectric properties of cement-based composite material by ionic liquid
CN108264302A
Cement concrete pavement energy conversion device and preparation method thereof
CN112047675A